Physical activity is associated with knowledge and attitudes to diabetes Type 2 in elderly - Alisson Padilha de Lima; Tânia Rosane Bertoldo Benedetti; Luma Zanatta de Oliveira; Suzane Stella Bavaresco; Cassiano Ricardo Rech (Journal of Physical Education (Maringá), 2018)
The aim this study was examined the association between physical activity, sociodemographic variables, health conditions and disease knowledge and attitudes in older adults with type 2 diabetes (DM2). A questionnaire for the collection of sociodemographic data and health conditions, the International Physical Activity Questionnaire (IPAQ), Diabetes Knowledge Scale (DKN-A), and Diabetes Attitude Questionnaire (ATT-19) were applied to 204 older adults. The absolute and relative frequencies was obtained and the results were analyzed by the chi-square test for proportions, bivariate analysis and logistic regression (p≤0.05). Significant associations were observed between being physically active and age above 70 years (OR=0.40; 95%CI: 0.22-0.90), having good knowledge of DM2 (OR=12.7; 95%CI: 6.8-30.1), and having a positive attitude towards DM2 self-care (OR=10.1; 95%CI: 6.34-20.1). Physical activity is associated with greater knowledge and a positive attitude towards DM2 self-care.